Irreversible Adsorption of Particles on Surface Features of a Circular and Rectangular Shape - Zbigniew Adamczyk; Jakub Barbasz (Adsorption Science & Technology)
The irreversible adsorption of spherical particles on surface features of various shapes (collectors) was studied using the Random Sequential Adsorption (RSA) model. Collectors in the form of circles and rectangles were considered, including the limiting cases of squares. Numerical simulation of the Monte Carlo type enabled the particle configurations to be determined, together with their density distribution (coverage) and the saturation coverage for various collectors to particle size ratio L̅ = L/2a and collector width to particle size ratio b̅ = b/2a. An unexpected feature found in these calculations was that the local coverage distribution of adsorbed particles was highly non-uniform, exhibiting a maximum at the centre and at the periphery of these collectors. The main finding of these calculations was the averaged number of particles <N p > adsorbed at the saturation state on collectors as a function of the L̅ and b̅ parameters. It was revealed that <N p > was highest for the square collector (for a fixed value of L̅). For L̅ > 5, our numerical results could be well approximated by the analytical expression <N p > = Θ ∞ L̅ 2 for circles, <N p > = 4Θ ∞ L̅ 2 π for squares and <N p > = Θ ∞ b̅L̅ 2 /π for rectangles. It was demonstrated that the theoretical results are in an agreement with experimental data obtained for latex particles adsorbed onto patterned surfaces obtained by a polymer-on-polymer stamping technique for gold-covered silicon and on photolithographically-patterned silane layers on silica.